2022
DOI: 10.22541/au.164796958.87011150/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Learning takes time: Biotic resistance by native herbivores increases through the invasion process.

Abstract: As invasive species spread, the ability of local communities to resist invasion depends on the strength of biotic interactions. Evolutionarily unused to the invader, native predators or herbivores may be initially wary of consuming newcomers, allowing them to proliferate. However, these relationships may be highly dynamic, and novel consumer-resource interactions could form as familiarity grows. Here, we explore the development of effective biotic resistance towards a highly invasive alga using multiple space-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…Opportunity may arise from dispersal movements including both spontaneous colonization (as in our model) and human‐assisted movements as in the case of exotic and invasive species of either non‐native consumers or resources (Litt & Pearson, 2022; Santamaría et al., 2022). In such cases, ecological opportunity is a determinant of invasion success of a (pest) species (Bras et al., 2022) or, alternatively, of the potential of biotic control by the native consumer community (Santamaría et al., 2022). Invasive species have been identified as a major conservation challenge (Gougherty & Davies, 2021), and multiple frameworks have been developed to quantify ecological opportunity in that particular case.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Opportunity may arise from dispersal movements including both spontaneous colonization (as in our model) and human‐assisted movements as in the case of exotic and invasive species of either non‐native consumers or resources (Litt & Pearson, 2022; Santamaría et al., 2022). In such cases, ecological opportunity is a determinant of invasion success of a (pest) species (Bras et al., 2022) or, alternatively, of the potential of biotic control by the native consumer community (Santamaría et al., 2022). Invasive species have been identified as a major conservation challenge (Gougherty & Davies, 2021), and multiple frameworks have been developed to quantify ecological opportunity in that particular case.…”
Section: Discussionmentioning
confidence: 99%
“…These associations, however, evolved under constraints (e.g., intra‐specific competition and predation pressure) and do not necessarily constrain a species to innately preferred resources. Successful use of alternative resources has been documented (e.g., James Reynolds et al., 2019; Santamaría et al., 2022; Wellenreuther et al., 2022), and the ability of species to opportunistically exploit novel suitable resources has, for example, been linked to range‐shifting potential in butterflies (Braschler & Hill, 2007; Graves & Shapiro, 2003; Pateman et al., 2012), other insects (Branco et al., 2015), squamates (Li & Wiens, 2022), and reef fishes (Monaco et al., 2020). Behavioural plasticity is widely considered to be one of the main mechanisms through which animals deal with novel environmental challenges (Sol et al., 2013) including during species' range shifts under climate change (Chevin & Lande, 2011; Valladares et al., 2014).…”
Section: Introductionmentioning
confidence: 99%
“…However, in cases were generalist herbivores populations are well conserved and are able to graze on exotic algae, they can be harmful and hinder the NIS macroalgae propagation (Cebrian et al 2011; Neilson et al 2018; Noè et al 2018). The effects of herbivores species on NIS macroalgae depend of some aspects like interspeci c competition between NIS and native macroalgae (Noè et al 2018) or the invasion history in the invaded area (Santamaría et al 2022). In this sense, Santamaría et al (2022) reported that native herbivores learn to consume the invader progressively (within less than a decade).…”
Section: Introductionmentioning
confidence: 99%
“…The effects of herbivores species on NIS macroalgae depend of some aspects like interspeci c competition between NIS and native macroalgae (Noè et al 2018) or the invasion history in the invaded area (Santamaría et al 2022). In this sense, Santamaría et al (2022) reported that native herbivores learn to consume the invader progressively (within less than a decade). Thus, at recent sites of invasion the herbivores ignore the alga, shifting to distinct preferences and high consumption rates at older sites (Santamaría et al 2022).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation